2016
DOI: 10.5751/es-08378-210213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of farmer social status and plant biocultural value on seed circulation networks in Vanuatu

Abstract: ABSTRACT. Seed circulation among farmers, which is embedded in composite social networks, is a key process in the dynamics of seed systems that shape crop diversity. We analyzed the daily circulation of biological objects, i.e., cultivated plants (31 species, 284 landraces), within a community of first-generation migrants (16 households, 30 persons) living on the island of Vanua Lava in the South Pacific archipelago nation of Vanuatu. By combining participant observation, ethnobiological inventories, and socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Gwodegree − (edges clustered > random) for prestige: success increases popularity + (edges clustered < random) for rarity: limited sharing maintains rarity (Labeyrie et al, 2015;Levy, 2016;Thomas & Caillon, 2016) Node connectivity variables Age (count) Nodeocov + for prestige: older individuals tend to be asked for knowledge (Henrich & Broesch, 2011;Bond & Gaoue, 2020) Knowledge (count or continuous) Nodeocov + for prestige: skillful individuals tend to be asked for knowledge (Henrich & Broesch, 2011;Santoro et al, 2020;Bond & Gaoue, 2020) Knowledge uniqueness score (continuous) Nodeocov + for rarity: because individuals with unusual information tend to be asked for knowledge (Bond & Gaoue, 2020) Node pair variables Spouse/kin (binary matrix) Edgecov + for homophily: spouses and genetically related people tend to share knowledge (Salali et al, 2016;Bond & Gaoue, 2020) Age (count) Absdiff − for homophily: peers tend to share knowledge (Salali et al, 2016) + for prestige: knowledge is more likely to be shared from older to younger (Henrich & Broesch, 2011) Knowledge (count or continuous) Absdiff − as control variable: individuals who say they share knowledge should have similar knowledge (Shalizi & Thomas, 2011;Santoro et al, 2020;Bond & Gaoue, 2020).…”
Section: Popularitymentioning
confidence: 99%
“…Gwodegree − (edges clustered > random) for prestige: success increases popularity + (edges clustered < random) for rarity: limited sharing maintains rarity (Labeyrie et al, 2015;Levy, 2016;Thomas & Caillon, 2016) Node connectivity variables Age (count) Nodeocov + for prestige: older individuals tend to be asked for knowledge (Henrich & Broesch, 2011;Bond & Gaoue, 2020) Knowledge (count or continuous) Nodeocov + for prestige: skillful individuals tend to be asked for knowledge (Henrich & Broesch, 2011;Santoro et al, 2020;Bond & Gaoue, 2020) Knowledge uniqueness score (continuous) Nodeocov + for rarity: because individuals with unusual information tend to be asked for knowledge (Bond & Gaoue, 2020) Node pair variables Spouse/kin (binary matrix) Edgecov + for homophily: spouses and genetically related people tend to share knowledge (Salali et al, 2016;Bond & Gaoue, 2020) Age (count) Absdiff − for homophily: peers tend to share knowledge (Salali et al, 2016) + for prestige: knowledge is more likely to be shared from older to younger (Henrich & Broesch, 2011) Knowledge (count or continuous) Absdiff − as control variable: individuals who say they share knowledge should have similar knowledge (Shalizi & Thomas, 2011;Santoro et al, 2020;Bond & Gaoue, 2020).…”
Section: Popularitymentioning
confidence: 99%
“…how farmers carefully evaluate trade-offs among its different contributions, some positive, some negative (Ango et al 2014), and also incorporate the complexity of their norms and values. Incentives for agrobiodiversity management rarely account for the diversity of local worldviews including social, spiritual and symbolic dimensions, while they affect a variety of domains of agrobiodiversity management including the spatial organization of crops in farmers' fields and in the landscape (Bonnemaison 1996), their selection beyond a purely utilitarian motivation (Caillon and LanouguĂšre-Bruneau 2005) and their circulation answering to social norms (Thomas and Caillon 2016).…”
Section: Social Network and Farms' Access To Agrobiodiversitymentioning
confidence: 99%
“…Although a higher percentage of women shared knowledge about the new methods compared to men, our analysis indicated that knowledge sharing was comparable between men and women and was not significantly related to the other characteristics examined. Work by Thomas and Caillon (2016) on the sharing of valuable plant cultivars suggests that social status may influence the degree to which valuable knowledge is shared. Further, other likely factors of importance are the ease with which (1) new processing methods can be directly observed by others (Macintyre and Foale 2013), and (2) the benefits for adopters are discernible and/or communicated by them.…”
Section: Characteristics Associated With Adoption and Knowledge Sharingmentioning
confidence: 99%